PERANCANGAN SISTEM INFORMASI PEMESANAN WEDDING ORGANIZER PADA SANGGAR KEMANTEN BERBASIS WEB - Marlina, Ines Bella; Ikhwani, Dinda Hanifah Nur; Setiawan, Afwan Budi (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Wedding organizer is one of the services that have a function to help the bride-to-be in preparing the planning and implementation of a series of wedding party events in accordance with the concept, schedule, and budget that has been set. Sanggar Kemanten wedding organizer rental information system is created by utilizing web-based information technology, with the aim of expanding the promotion area and simplifying the booking process. Wedding organizer rental information systems use PHP and MySQL programming languages, methods used on these systems using waterfall methods. Information system wedding organizer Sanggar Kemanten is very helpful for brides-to-be who do not want to bother with their wedding planning problems. With the development of technology today wedding organizer Sanggar Kemanten has started to move from manual process to online process that is information system wedding organizer that lined web.